The Effectiveness Of Principal Training In Improving Principal Performance: A Qualitative Study At The Bandung City Education Office - Dinar Samsunizar Pratama; Cepi Triatna; Asep Suryana (Universitas Nurul Jadid, 2026)
This study aims to analyze the effectiveness of principal training programs organized by the Bandung City Education Office in improving principals’ performance. The study employed a qualitative descriptive approach. Data were collected through in-depth interviews with the Secretary of the Bandung City Education Office, elementary school principals, and teachers. Data analysis was conducted using thematic analysis assisted by the NVivo application through data reduction, coding, categorization, theme development, and interpretation. The findings revealed that the principal training program was considered effective because the training materials were relevant to school needs, utilized varied learning methods, and were supported by follow-up activities such as monitoring and learning communities. The training contributed to improvements in instructional leadership, academic supervision, data-based decision making, organizational communication, and collaborative culture within schools. The implementation of training outcomes was influenced by supporting factors such as support from the Education Office, learning communities, and teamwork, as well as inhibiting factors including teacher resistance to change, limited infrastructure, and inadequate information technology skills. This study emphasizes that the effectiveness of principal training is determined not only by the quality of training materials but also by organizational culture and sustainable post-training mentoring.